Evidence of the Financial Audit - Raziūnienė, Daiva; Adaškevič, Uršula (Buhalterinės apskaitos teorija ir praktika, 2020)
Evidence is an argument that justifies the truth or falsity of a subjective opinion or assertion. Characteristics of audit evidence directly impact the obtaining process of sufficient audit evidence as well as determine the final audit decision regarding fairness and truthfulness of financial reporting. The purpose of the article is to identify the material aspects of evaluating audit evidence and to define the concept of the financial statement‘s audit evidence. The research methods applied in the article are comparative analysis and synthesis of Lithuanian and foreign scientific literature, interpretation, critical thinking and systematization of financial audit laws and regulations. Furthermore, the article examines the concept of financial audit evidence, its characteristics and criteria of reliability as well as disclosure of material audit evidence.
Keywords: financial audit; audit evidence; sufficiency; reliability; relevance